التحكم التناسبي التكاملي التفاضلي(PID) بمحركات التيار المستمر - داود, محسن (Latakia University Journal -Engineering Sciences Series, 2019)
إن اختيار خوارزمية التحكم المناسبة للنظم الديناميكية هو دوما الحل الوسط بين جودة التحكم وكلفته، وبالتالي اختيارالبنية الأبسط للتحكم. من المهم الملاحظة أن خوارزميات التحكم التي تحتوي على متحكمات من النوع PID تستخدم بشكل واسع في نظم التحكم بمحركات التيار المستمر وهي أكثر الطرق فائدة في تحقيق متطلبات التحكم, إلا إنها تتضمن بعض أوجه القصور. يقدم البحث تحليلا شاملا لاستجابة أنظمة التحكم بمحركات التيار المستمر بوجود إشارات التشويش وتغير بارامترات النظام. يظهر البحث مزايا ومساوئ استخدام المتحكمات من النوع PID في حلقة التحكم المغلقة بمحركات التيار المستمر. يوفر نموذج المحاكاة لمحرك التيار المستمر الوارد في البحث إمكانية التحليل السريع للسلوك الديناميكي للمحرك.يورد البحث مخططات المحاكاة لخوارزميات التحكم بمحركات التيار المستمر، التي تستخدم متحكمات مختلفة في برنامج Matlab. The choice of an appropriate control algorithm for dynamic systems has always been a compromise between the quality of control and its cost- hence choosing the simplest control structure. It is worth noting that PID algorithms are widely used in the control systems of DC motors; they are the most useful methods adopted to satisfy control requirements, but they have their own shortcomings. This study offers a comprehensive analysis of the response of DC motor control systems along with the presence of disturbance signals and variation in system parameters. This research shows the advantages and disadvantages of applying PID controllers to the closed-loop control of the DC motor. The DC motor simulation model in this research provides a fast analysis of motor dynamic behavior. In this study, there is a matlab simulation diagram of DC motor control algorithms.